Psychometric properties of the questionnaire of cognitive and affective empathy in a Portuguese sample - Queirós, Andreia (2018)
Empathy is an important concept in psychology and cognitive neuroscience. Despite the controversy around its definition, most researchers would agree that empathy is a multidimensional phenomenon which involves a vicarious experience of another person's affective state and an understanding of another person's affective experience. Self-report measures of empathy constitute an important tool for both research and clinical practice. The main goal of this study was to adapt and study the psychometric properties of the Questionnaire of Cognitive and Affective Empathy (QCAE), a worldwide used measure of empathy, in a Portuguese community sample (N = 562). Confirmatory factor analyses supported the factor structure of the original QCAE. Results show that the Portuguese version of the QCAE has sound psychometric properties, with good structural validity and internal consistency for both scales (i.e., affective and cognitive) and respective subscales of the instrument (i.e., Emotion Contagion, Proximal Responsivity, Peripheral Responsivity, Perspective Taking and Online Simulation). We tested both a five correlated factor structure (Model 1) and a second-order model that postulates the affective and cognitive dimensions (Model 2). Our results show that while both models present acceptable goodness of fit indices, Model 1 performs slightly better. In conclusion, the Portuguese version of the QCAE may prove a useful tool for future cross-cultural assessments of empathy in both research and clinical practice.